2010
DOI: 10.1002/pds.2089
|View full text |Cite
|
Sign up to set email alerts
|

Long term patterns of use after initiation of oral antidiabetic drug therapy

Abstract: This study shows that adherence to type 2 diabetes treatment guidelines for initial treatment is implemented on a large scale. Longitudinal patterns show that the majority of patients receive a small number of modifications to their drug regimen. Discontinuation rates were relatively low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
5
15
1
Order By: Relevance
“…These analyses were adjusted for the following variables of interest and available within the database: duration of follow up, gender, age, coverage scheme and initial antidiabetic agent. Similar variables have been found to be of significance in previous studies . Hazard ratios (HR) and CIs are presented.…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…These analyses were adjusted for the following variables of interest and available within the database: duration of follow up, gender, age, coverage scheme and initial antidiabetic agent. Similar variables have been found to be of significance in previous studies . Hazard ratios (HR) and CIs are presented.…”
Section: Methodssupporting
confidence: 77%
“…Pre‐existing CVD and management of newly diagnosed type 2 diabetes can therefore be a difficult issue for physicians . Little information has been published regarding antidiabetic agent use in the primary care setting amongst newly treated type 2 diabetes patients , and the majority of information published has come from the United States with no studies having looked at how pre‐existing CVD medicine use affects treatment patterns. This study aims to provide prescribers and other health care professionals with an understanding of drug utilization in newly treated type 2 diabetes, at the population level, in a European country.…”
Section: Introductionmentioning
confidence: 99%
“…The low discontinuation rates of metformin-based therapy may also suggest that approximately 80% of the patients are adequately treated over longer periods. Our analysis was consistent with that of recent studies [18][19][20]. These findings provide additional valuable information to clinicians, patients and the public regarding the adoption and safety of metformin as an initial medication for new diabetes patients.…”
Section: Discussionsupporting
confidence: 81%
“…This latter observation does not seem to be coherent as discontinuation would be associated with adequate glycaemic control; however, there will be patients restarting a different OAD shortly after discontinuing. When comparing the one-year persistence of initial OAD treatment with other published studies there was similarity with some studies [14,16], whilst there were clear differences with others [15]. The range of persistence rates can be explained by the settings where the studies were conducted, by the outcome definitions applied, and by the length of follow-up considered for the reported treatment changes.…”
Section: Discussionmentioning
confidence: 59%
“…A study conducted in PHARMO for the period 1999–2004 also reported sulfonylureas (53.2%) and metformin (40.2%) as the most frequently used initial OAD therapies [14]. Metformin use as first OAD therapy seems to be increasing in recent years in other countries as well [15]. …”
Section: Discussionmentioning
confidence: 99%